Pengaruh Electronic Traffic Law Enforcement (ETLE) dalam Membantu Proses Operasi Zebra - Angga Rusmika; Padimun Lumban Tobing; Robby Tejamukti (HUMANIORUM, 2023)
Traffic accidents are sudden and unintentional events that occur on the highway, involve vehicles without or with other drivers, and cause casualties and material losses. In order to avoid the possibility of other traffic violations, it is necessary to have law enforcement officers who are authorized and responsible for state security and order, namely the POLRI or the Indonesian National Police, as law enforcement tools, protectors, servants, and protectors of the community, as referred to in their main duties in Article 13 Law Number 2 of 2002 concerning the Indonesian National Police. The development of information in the all-digital era creates special hope and pressure for the police to improve their performance in serving, protecting, and controlling public order. ETLE became the answer to these demands. This journal uses normative legal research methods. The problem approach used is the case approach. The technique of tracing legal materials uses a literature study technique as well as an analysis of the study using qualitative analysis. Based on the research results, the authors can conclude that ETLE is capable of being a means to improve results in Zebra operations. ETLE has proven to be able to find various types of traffic violations, as evidenced by the increasing number of violations using seat belts after the application of ETLE. In addition, ETLE gives motorists a wary attitude for fear that CCTV will record their traffic violations. This has to do with the driver's efforts to obey traffic rules.